Ruptured caesarean scar ectopic pregnancy: a rare case report - Jain, Shikha; Chaudhary, Swati; Jain, Neha; Ranjan, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Caesarean scar pregnancy is a rare type of ectopic pregnancy. Little is known about its incidence and natural history. With increasing incidence of caesarean section worldwide, more and more cases are diagnosed and reported. We report a case of caesarean scar site ruptured ectopic pregnancy presented to emergency department with hypovolemic shock. Decision for emergency laparotomy was taken on the basis of clinical findings and ultrasonography. Hemoperitoneum of 2 litres with scar site rupture ectopic was seen. Evacuation of products along with repair of uterus in 2 layers with bilateral tubal ligation was done. It is the rarest kind of ectopic pregnancy and may lead to severe life threatening complications such as uterine rupture and severe hemorrhage or may have adverse effect on future fertility.